Allergen immunotherapy in pregnancy. Issue 1 (December 2015) - Oykhman, Paul; Kim, Harold; Ellis, Anne
Abstract Background Allergic diseases such as asthma and allergic rhinitis constitute a significant burden of disease among women of childbearing age and those who are pregnant. Adequately managing these conditions is paramount in reducing negative fetal outcomes as well as maternal complications during pregnancy. However, the potential for harm to both the mother and fetus demands carefully balancing efficacy and safety of treatment. Allergen immunotherapy (AIT) has emerged as a relatively safe and efficacious mode of therapy in both children and adults. AIT has also been considered for use during pregnancy. Methods A review of the literature was conducted for data regarding the safety of initiation and continuation of AIT during pregnancy as well as the effect of AIT on the development of atopy in offspring. MEDLINE and the Cochrane Library were searched for clinical trials, randomized control trials, observational studies and journal articles in English using the terms "Pregnancy" and "Immunotherapy" from 1900 to present. This yielded 4 studies (totaling 422 pregnancies receiving AIT) investigating the continuation of AIT in pregnancy, 2 (totaling 31 pregnancies receiving AIT) evaluating AIT initiation during pregnancy and 5 observing the effect of AIT on atopy in offspring. Results No significant difference was found in the incidence of prematurity, hypertension (HTN)/proteinuria, congenital malformations or perinatal deaths between the women continued on AIT (both subcutaneous (SC) IT and sublingual (SL) IT to inhalant allergens as well as venom IT) during pregnancy and controls. Similarly, there was no significant difference in maternal or fetal complications between pregnant women initiated on AIT and controls. Among the few pregnant women (10/453 pregnancies) who experienced generalized reactions while receiving AIT, none were found to have fetal complications. Neither SCIT nor SLIT during pregnancy altered the risk of developing atopic disease in offspring. Conclusions Based on these data, the continuation of AIT during pregnancy appears safe. Furthermore, the few data available suggest that the initiation of AIT during pregnancy might also be safe, however, more data is required for a definitive conclusion. Lastly, available studies do not show a convincing reduction in the development of atopy in offspring from the administration of AIT during pregnancy.